Retention of metallic and non-metallic double-crown-retained mandibular overdentures on implants: An in-vitro study. Issue 4 (October 2020) - Elkabbany, Aya; Kern, Matthias; Elkhadem, Amr H.; Wille, Sebastian; A. Amer, Ashraf; Chaar, M. Sad
Abstract: Purpose: To evaluate the change in the retention of novel metallic and non-metallic combinations for double-crown-retained mandibular overdentures on implants. Methods: Cylindrical bases were used to insert four implants arranged in an arch, with 10 mm inter-implant spacing anteriorly, and 35 mm posteriorly. Five groups ( n = 8 each) of different materials combinations were tested for retention: zirconia abutments/PEEK framework (ZP), PEEK abutments/PEEK framework (PP), titanium abutments/PEEK framework (TP), titanium abutments/CoCr framework (TC), and titanium abutments/gold copings/cobalt-chromium framework as the control group (TG). The abutment retention height was 4 mm with 1° convergence angle. The retention was measured in a wet condition using a chewing simulator initially, and then at 100, 200, 500, 1, 000, 2, 000, 3, 000, 5, 000, 8, 000, and 10, 000 insertion/separation cycles, which simulates the removing and inserting of an overdenture three times daily for 10 years of function. Results: The initial median retention of all groups ranged from 10.0 to 33.3 N. After 10, 000 insertion/separation cycles, the median retention ranged from 10.3 to 35.0 N. The change in the retention after 10, 000 cycles was not statistically significant within groups ZP and TG. For groups PP and TP, there was a slight increase in retention with partial significance. The retention of group TC showed fluctuation with a partially significant decrease in retention. Conclusions: The use of novel metallic and non-metallic combinations in the construction of double-crown-retained mandibular overdentures on implants resulted in acceptable levels of retention and might be recommended for clinical application.